ROLE OF SIKKIM STATE COOPERATIVE BANK LTD. IN FINANCIAL INCLUSION (International Journal of Food and Nutritional Sciences, 2022)
The expansion of access to financial services is a priority of India's government. When we talk about "financial inclusion," we're referring to the practice of making banking services and credit available to low-income people at prices they can afford. India's central bank, the Reserve Bank of India, and the government have both implemented policy changes to advance financial inclusion as a priority for the country. Cooperatives are seen as crucial in this effort because of the impact they can have on the economies of underserved communities that may benefit from access to banking and financial services. The purpose of this research is to learn why Sikkim State Cooperative Bank Ltd. is crucial to promoting economic prosperity for all people in Sikkim. This research aims to determine the barriers and facilitators to financial inclusion in Sikkim's cooperative sector.